Bloodstream Infections Leading to Sepsis: Clinical and Microbiological Profiling of Bacteremia among Hospitalized Patients in Surabaya, Indonesia - Nuritsna Marwasyifa; Tri Pudy Asmarawati; Firman Setiawan; Pepy Dwi Endraswari (Current Internal Medicine Research and Practice Surabaya Journal)
Introduction: Bacteremia poses a significant health risk due to its frequently atypical presentation and potential progression to sepsis. Understanding its clinical profiles and causative pathogens is essential for timely diagnosis and effective management. This study examined the characteristics of bacteremia cases in 2022 at Universitas Airlangga Hospital, Surabaya, Indonesia.